Organization of objective structured clinical examination (OSCE) for third course dental students - Біденко, Н. В. (Actual Dentistry, 2019)
Summary. The experience and results of organization and realization of objective structured clinical examination (OSCE) for third course dental students are presented. The examination consisted of practical skills control concerning different fields of dentistry and general medical skills. Key words: high stomatological education, OSCE for dentists, practical skills for dental students.